FLT3, a prognostic biomarker for acute myeloid leukemia (AML): Quantitative monitoring with a simple anti-FLT3 interaction and flow cytometric method - Chadarat Ampasavate (2019)
© 2019 The Authors. Journal of Clinical Laboratory Analysis Published by Wiley Periodicals, Inc. Background: Overexpression of fms-like tyrosine kinase 3 (FLT3) protein in leukemia is highly related to poor prognosis and reduced survival rate in acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) patients. Simple but efficient quantification of FLT3 protein levels on the leukemic cell surface using flow cytometry had been developed for rapid determination of FLT3 on intact cell surface. Methods: Quantitation protocol for FLT3 biomarker in clinical samples was developed and validated. Cell model selection for calibration curve construction was identified and evaluated. Selected antibody concentrations, cell density, and incubation time were evaluated for most appropriate conditions. Comparison of the developed FLT3 determination protocol with the conventional Western blot analysis was performed. Results: EoL-1 cell line was selected for using as positive control cells. Calibration curve (20%-120% of FLT3 positive cells) and quality control (QC) levels were constructed and evaluated. The results demonstrated good linearity (r 2  > 0.99). The intra- and inter-day precision and accuracy, expressed as the coefficient of variation (%CV) and % recovery, were <20% and fell in 80%-120% in all cases. When compared with Western blotting results, FLT3 protein expression levels in leukemia patient's bone marrow samples were demonstrated in the same trend. Conclusions: The effective, reliable, rapid, and economical analytical technique using the developed flow cytometric method was demonstrated for FLT3 protein determination on leukemic cell surface. This method provided a practical analysis of FLT-3 biomarker levels which is valuable for physician decision in acute leukemia treatment.